Penggunaan E-Modul Di Sekolah Menengah Kejuruan Pada Mata Pelajaran Simulasi Digital - Rahmadhani, Sri; Efronia, Yulia (Universitas Negeri Padang, 2021)
Electronic-based media or often reffered as e-module is elearning media that povide visualization that can be accesed through electronic media. Recently, many e-module have been developed by using several methods. The result obtained is effectiveness of using e-module that can be implemented at vocational schools, especially in digital simulation subject, ehich is reported to be very good. The use of e-module positively impacts on student learning outcome and obtains high student responses.